COMPOSITIONAL RESEARCH IN CONTEMPORARY NOVELS - Sanobar Karimova Mirzayevna (American Journals Publishing, 2025)
This article explores the compositional strategies employed in contemporary novels, focusing on narrative structure, thematic integration, and stylistic innovation. Through a detailed literature analysis and empirical methods, it examines how modern authors construct their works to engage readers and convey complex ideas. The study aims to identify trends, assess their impact, and provide insights for scholars and writers.
Keywords: Contemporary novels, narrative structure, thematic integration, stylistic innovation, compositional strategies, reader engagement.